Primary cutaneous infections with non-tuberculous mycobacteria: a report of 6 cases - Qi-Hao Yao; Hui-Lin Zhi; Xiu-Jiao Xia; Ze-Hu Liu (BMC Infectious Diseases)
Abstract Background The incidence of non-tuberculous mycobacterium infection has shown a gradual increasing trend in recent years, among which cutaneous manifestations as an important aspect. This study aimed to describe the clinical features and microbiological findings in 6 cases of primary cutaneous nontuberculous mycobacterium infection. Methods In this retrospective study from June 2021 to June 2022, the clinical data and microbiological results of six cases diagnosed with primary cutaneous non-tuberculous mycobacterium infection in department of dermatology, Hangzhou Third People’s Hospital were analyzed. Results All six cases were primary cutaneous non-tuberculous mycobacterium infections, four of which had a history of trauma or exposure, and two had an underlying disease that could lead to compromised immunity. All patients presented with erythema nodular skin lesions, four on the upper or lower extremities, one on the face, and one on the right hip. The histopathological findings of five patients who underwent biopsy were granulomatous inflammatory changes with mixed infiltration. Laboratory cultures using tissue or tissue fluid were all successful, including four Mycobacterium marinum, one Mycobacterium abscessus, and one Mycobacterium avium. Metagenomics next-generation sequencing detected results consistent with culture colonies in only two cases. With the exception of case 4, all patients responded well to oral medication, with a course of treatment ranging from 4 months to 1 year, and the prognosis was good. Conclusions The clinical features of primary cutaneous non-tuberculous mycobacterium infection are often lacking in specificity, and the identification of related strains is difficult for a variety of reasons. Although the results of metagenomics next-generation sequencing are useful for pathogen spectrum identification, its diagnostic value should be carefully reevaluated under certain circumstances. Patients with suspected triggers who do not respond well to conventional treatments should be suspected as atypical infection and potential immunosuppression. If diagnosed and treated promptly, the prognosis of primary cutaneous non-tuberculous mycobacterium infection is generally good.